Pengaruh PAD dan Dana Perimbangan terhadap IPM - Ani Diya Kanita Al Sihab; Karolina A. Rewa; Yuniarti Reny Renggo (AKUNTANSI 45, 2026)
This study aims to analyze the influence of Regional Original Revenue (PAD) and Balance Funds on the Human Development Index (HDI) in 21 districts and 1 city in East Nusa Tenggara province in 2021-2025. This research is motivated by the low level of human development in several areas in East Nusa Tenggara Province and the high dependence of local governments on transfer funds from the central government. The approach used in this study is a quantitative approach using secondary data from the Central Statistics Agency of East Nusa Tenggara Province and the Directorate General of Financial Balance. The analysis technique used was panel data regression with the help of the Eviews8 program. The results of the analysis showed that Regional Original Revenue (PAD) had a positive but insignificant effect on the Human Development index (HDI), while the Balance Fund had a positive and significant effect on HDI in East Nusa Tenggara Province. Together, PAD and the Balance Fund have a positive effect on HDI. The results of this analysis show that the Balance Fund is still the main source of financing human development in East Nusa Tenggara Province because of the limited capacity of regional PAD. Therefore, local governments need to increase the effectiveness of PAD management and optimize the use of the Balance Fund so that human development can increase evenly and sustainably.